Cephalometric variations of the angles formed by the skull anterior base plane, palatine plane and mandibular plane in adenoid patients before an after surgery - Llana Gagliuffi, Jan Helmy (2005)
Presently work the variations cefalométricas of the angles was studied formed by the planes base previous of the skull, palatine and mandibular in 60 adenoid patients that arrived to the departament of Odontopediatry and the service of Otorrinolaringología of the Naval Medical Center during the year 2001 who you/they were intervened surgically (adenoidectomía) The lateral cefalogramas of the 60 patients was studied with adenoid hipertrofia that were operated two years ago approximately of the adenoides who were selected bused on their clinical histories For tt was necessary the gathering of the x rays lateral surgzcal pre and the taking of the lateral x-rays after 2 years approximately, that is to say in the year 2003, of the surgical operation Where one kept in mind the analyses of Steiner and of Schwartz, for it was made it the lrnes cefalométricos,necessary for the present study, of the following planes - plane Bases previous of the skull (SN) , Palatine plan (ENA-ENP) Y Plano Mandibular (Go-Gn)